ITERATION FACTORS METHOD FOR MULTILEVEL RADIATIVE TRANSFER: CONVERGENCE PROPERTIES - Kuzmanovska, Olgica; Atanackovic, Olga (Astronomical Observatory of Belgrade, 2010)
We present the Iteration Factors Method (IFM) developed to solve the multilevel line transfer problem and show its excellent convergence properties in the well-known five-level Ca II test case.